(untitled) (Pravaha, 2020)
The study aims to examine the impact of liquidity on the profitability of Nepalese commercial banks. Investment ratio, capital ratio and liquidity ratio are the independent variables and return on assets is dependent variable. Secondary sources of data have been used from the annual reports of sampled commercial banks. The regression models are estimated to test the effect of bank liquidity on performance of Nepalese commercial banks. Study results reveal that investment ratios and liquidity ratios are negatively related to return on assets indicating that higher the investment ratios and liquidity ratios, lower would be the return on assets and vice versa. Further, the relationship between capital ratios and return on assets is found to be positive indicating that higher the capital ratios of the bank, higher would be the return on assets. Similarly, beta coefficient for capital ratio is positively significant with bank performance, which indicates that increase in capital ratio leads to increase the performance of the banks. However, beta coefficients for investment ratio and liquidity ratio are negative with return on assets indicating increased liquidity ratio and investment ratio decrease the return on assets of the bank.